(untitled) (Medico Legal Update, 2020)
The aims of this study are knowing of cardiac functional Efficiency level and circulatory system for the short, middle and long -distance runner and knowing the differences of the cardia physical efficiency level and circulatory system for the long-middle and shirt-distance runners. Thus, continuing of the sport training operation may lead to take place some of the physiological changes in body, as the track and field games is definitely distinguished that runners. The athletes may face a various kind of functional changes resulted by various training resilience. While the Heartbeat size increases with the physical efficiency level at the relation time. Thus, we may say that physical efficiency level increases and reflects with the Heartbeat increasing and lowering of the cardiac Heartbeat during relaxation. As the track and field races are dividing athletes into short, middle and long-distance runners. Generally, the athletes participating may face in various games, therefore, the research importance is based on knowing the cardia physical efficiency level and circulatory system for the short, middle long-distance runners, then attempting to know the best set in fitness in raspatory circulatory system among the athletes in these activities.